(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
A study was conducted on Ficus species to evaluate its role in avifauna conservation Jahangirnagar University campus from December 2012 to September 2013. Ficus benghalensis and Ficus rumphii were found to provide food and shelter to the bird community of Jahangirnagar University throughout the year because of their asynchronous fruiting. A total of twenty four Ficus trees were selected for the study. Number of fruit providing trees varied in different months (? = 11.6, range = 4-22, sd ± 6.29). Twenty seven species of birds were recorded from Ficus spp. throughout the year. Dependency of bird species on Ficus varied in different months ( ? = 18.1, sd ± 2.42, range = 16-22). Common Myna was found to visit Ficus tree more frequently while Oriental White Eye was less frequent. The height of the studied Ficus benghalensis ranged from 17 45 feet with the mean ? = 26.67 ± 7.51 while Ficus rumphii ranged from 30-48 feet with the mean ? = 39.33 ± 9.0. Jahangirnagar University J. Biol. Sci. 3(2): 9-16, 2014 (December)